2017
DOI: 10.1111/1541-4329.12111
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cross‐Disciplinary Teaching and a Wiki Research Project to Engage Undergraduate Students’ to Develop Information Literacy, Critical Thinking, and Communication Skills

Abstract: A Wiki research project was created in the Functional Foods for Health (FST/HNFE 2544) as an instructional tool and assignment for improving undergraduate students' proficiency in evaluating appropriate information sources for rapidly evolving science and research. The project design targeted improving students' information literacy skills including how students obtain, discern relevant and reliable scientific information from propaganda, critique information, and communicate scientific language. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…Other studies have shown a correlation between critical thinking skills and information literacy. Crist, et al (2017) conducted a study combining critical thinking, information literacy, and communication. The results show that learning provides opportunities to explore and expand content in scientific research.…”
Section: Correlation Between Critical Thinking and Information Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown a correlation between critical thinking skills and information literacy. Crist, et al (2017) conducted a study combining critical thinking, information literacy, and communication. The results show that learning provides opportunities to explore and expand content in scientific research.…”
Section: Correlation Between Critical Thinking and Information Literacymentioning
confidence: 99%
“…Information literacy is closely related to critical thinking skills. Critical thinking skills are related to exploring and evaluating information to form opinions with relevant and valid information (Crist et al, 2017). It includes analyzing information, then synthesizing the information for explaining the argumentation and solving problems based on problem context.…”
mentioning
confidence: 99%
“…It can also challenge evaluators hoping to understand what kinds of ML education work best and how ML education can be implemented effectively. Extant research about the effectiveness of ML education focuses on various skills, such as understanding that media images are often unrealistic (Fingar and Jolls, 2014), critically evaluating and applying research to problems (Crist, Duncan, and Bianchi, 2017), detecting bias, and interpreting news stories (Tully, Vraga, and Smithson, 2020), among other skills. The wide-ranging interpretations of ML competencies pose challenges in aggregating research on the effectiveness of ML educational interventions.…”
Section: Identifying Media Literacy Learning Expectationsmentioning
confidence: 99%
“…www.rand.org Alice Huguet | Garrett Baker | Laura S. Hamilton | John F. Pane ML education work best and how ML education can be implemented effectively. Research about the effectiveness of ML education has focused on a variety of skills, such as understanding that media images are often unrealistic (Fingar and Jolls, 2013), critically evaluating and applying research to problems (Crist, Duncan, and Bianchi, 2017), detecting bias and interpreting news stories (Tully, Vraga, and Smithson, 2020), and others. The wide-ranging interpretations of ML competencies pose challenges in aggregating research on the effectiveness of ML educational interventions.…”
Section: Media Literacy Standards To Counter Truth Decaymentioning
confidence: 99%